OA35 Efficacy of secukinumab and HLA-B27 subtypes: results from a Phase 3b randomised controlled trial in axial SpA. (23rd April 2022) - Marzo-Ortega, Helena; Poddubnyy, Denis; Pournara, Effie; Schulz, Barbara; Deodhar, Atul; Baraliakos, Xenofon
Abstract: Background/Aims: Human Leukocyte Antigen (HLA)-B is strongly associated with axial spondyloarthritis (axSpA); over 100 subtypes of HLA-B27 are currently recognized and designated as HLA-B∗2701 to HLA-B∗27106. The association of these subtypes with clinical features of axSpA patients or their response to therapy has not been determined. This post hoc analysis explored the potential association of the HLA-B27 subtypes with the effect of secukinumab in axSpA patients from the SKIPPAIN trial (NCT03136861). Methods: SKIPPAIN, a 24-week, randomised, double-blind, placebo-controlled, multicentre trial, enrolled adult axSpA patients with active disease fulfilling ASAS classification criteria (Bath Ankylosing Spondylitis Disease Activity Index [BASDAI] score ≥4 and average spinal pain numerical rating scale [NRS] score >4 at baseline) and inadequate response to ≥ 2 NSAIDs for ≥4 weeks. Patients were randomised (3:1) to receive subcutaneous secukinumab 150 mg or placebo weekly followed by every 4 weeks (q4w) starting at Week 4. At Week 8, placebo patients were re-randomised to secukinumab 150 or 300 mg q4w up to Week 24. HLA-B27 subtypes were tested by PCR-reverse sequence-specific oligonucleotide probe on a baseline blood sample. Average spinal pain scores were analysed using a repeated measures analysis of covariance model. Results: Overall, 380 patients with axSpA (269 [70.8%] AS; 111 [29.2%] nr-axSpA) were randomised to secukinumab 150 mg (n = 285) or placebo (n = 95). Most patients were HLA-B27 positive in both treatment groups (233 [81.8%] SEC vs 76 [80.0%] placebo). Distribution of HLA subtypes was consistent with what is expected in a typical European population, with HLA-B*27:05:02G as the most common allele (secukinumab 150 mg, n = 172 [60.4%]; placebo, n = 48 [50.5%]). In the HLA-B*27 homozygous group, a higher proportion of patients had uveitis, peripheral arthritis, enthesitis and a family history of spondyloarthritis versus the heterozygous group; disease severity or burden of disease was similar between the two groups. Male predominance was more evident in the HLA-B*27 homozygous group, who were younger by 1 year and reported longer duration of symptoms by an average of 8 months. Disease severity was comparable while disease burden was higher in the B*27:05:02G versus the B27:02:01G heterozygous group. There was a significant least square (LS) mean difference (standard error [SE]) in back pain response between secukinumab and placebo in HLA-B27 positive patients (-0.9 [±0.27], 95% confidence interval [CI] -1.47 to -0.42, P = 0.0004) and HLA-B27 heterozygous (B*27:05:02G) patients (-0.9 [±0.37], 95% CI − 1.62 to -0.17, P = 0.0152), differences in other HLA-B27 subtypes were non-significant. Conclusion: Although secukinumab has shown efficacy in both HLA-B27 positive and negative patients, presence of HLA-B27 and homozygosity had a distinct positive effect on response. Further studies or pooled analyses are warranted to investigate associations of HLA-B27 subtypes with the clinical features of axSpA or of less prevalent HLA-B27 subtypes with treatment response. Disclosure: H. Marzo-Ortega: Consultancies; AbbVie, Amgen, BMS, Biogen, Celgene, Gilead, Janssen, Lilly, Novartis, Pfizer, Samsung Bioepis, Sanofi-Aventis, UCB. Grants/research support; Amgen, Lilly, Janssen, Pfizer, Sandoz, Sanofi, Galapagos. D. Poddubnyy: Consultancies; AbbVie, Biocad, BMS, Eli Lilly, MSD, Novartis, Pfizer, Samsung Bioepis, UCB, Gilead. Member of speakers' bureau; AbbVie, BMS, Lilly, MSD, Novartis, Pfizer, UCB. Grants/research support; AbbVie, MSD, Eli Lilly, Novartis, Pfizer. E. Pournara: Shareholder/stock ownership; Novartis. Other; Employee of Novartis. B. Schulz: Other; Employee of Novartis. A. Deodhar: Consultancies; AbbVie, Amgen, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Eli Lilly, Gilead, GSK, Janssen, Novartis, Pfizer, UCB. Member of speakers' bureau; AbbVie, Amgen, Boehringer Ingelheim, Bristol Myer Squibb, Eli Lilly, GSK, Janssen, Novartis, Pfizer, UCB. Grants/research support; AbbVie, Eli Lilly, GSK, Novartis, Pfizer, UCB. X. Baraliakos: Consultancies; AbbVie, BMS, Celgene, Chugai, Galapagos, Gilead, MSD, Novartis, Pfizer, UCB. Member of speakers' bureau; AbbVie, BMS, Celgene, Chugai, MSD, Novartis, Pfizer, UCB. Grants/research support; AbbVie, Novartis.